Exploring disruptive power: Acceptance of digital technologies in mechanical engineering education among Ghanaian technical university teachers - Emmanuel Obobi Tettehfio; Agus Setiawan; Iwan Kustiawan; Prince Yaw Andoh (Jurnal Pendidikan Vokasi, 2023)
The paper examines the effect of perceived ease of use, user acceptance, and quality assurance practices on the acceptance of digital technology among mechanical engineering teachers in Technical Universities in Ghana. The paper adopts a quantitative research approach using a descriptive survey design. A sample of 167 mechanical engineering teachers was selected using stratified and simple random sampling techniques. Data was collected through a structured questionnaire that included demographic information and variables related to digital technology acceptance. The collected data were analyzed using structural equation modeling with the aid of SmartPLS 4 software. The study's findings reveal that perceived ease of use, user acceptance, and quality assurance practices significantly and positively influence mechanical engineering teachers' acceptance of digital technology. Specifically, the acceptance of quality assurance practices was found to have the strongest impact on technology acceptance among the three factors examined. The study focused on mechanical engineering teachers in Ghana's Technical universities, limiting the generalizability of the findings to other educational contexts. Future research should consider expanding the sample size and including participants from different educational institutions and other disciplines. This study contributes to the existing literature on digital technology acceptance by examining the specific context of mechanical engineering education in Ghana. The findings also contribute to the broader discourse on digital skills development and closing the digital divide in educational settings.